Cutaneous squamous cell carcinoma (cSCC) and immunosurveillance – the impact of immunosuppression on frequency of cSCC. (13th December 2019) - Plasmeijer, E.I.; Sachse, M.M.; Gebhardt, C.; Geusau, A.; Bouwes Bavinck, J.N.
Abstract: Solid organ transplant recipients (OTR) are at extreme risk of developing cutaneous squamous cell carcinomas (cSCC) post‐transplantation due to the immunosuppressive medication needed to retain the transplanted organ. The early classical immunosuppressive drugs, azathioprine and cyclosporine, have largely been replaced by modern immunosuppressants, namely mycophenolate mofetil and tacrolimus, as well as sirolimus and everolimus. Although still very high, the risk of cSCC in OTR seems to be decreasing which suggests that cSCC risk may be lower in OTR treated with these modern immunosuppressive drugs and that cSCC preventive measures may be effective. OTR should be closely monitored so that cSCC can be treated at an early stage. (Chemo)prevention of cSCC as well as changing immunosuppression to more favourable regimens will be important in future to reduce skin cancer incidence.